The impact of nutritional intervention on quality of life and outcomes in patients with head and neck cancers undergoing chemoradiation - Cardellini, Sara; Deantoni, Chiara Lucrezia; Paccagnella, Matteo; Casirati, Amanda; Pontara, Andrea; Marinosci, Alessandro; Tresoldi, Moreno; Giordano, Leone; Chiara, Anna; Dell’Oca, Italo; Di Muzio, Nadia Gisella; Caccialanza, Riccardo; et al. (Frontiers in Oncology, 2024)
IntroductionChemoradiotherapy in head and neck cancer patients has a curative intent but often deteriorates nutritional status leading to sarcopenia and cachexia.MethodsIn this observational and single-centered study, a prospective evaluation of several biochemical and anthropometrical parameters, weight loss, handgrip strength, visual analogue scale of appetite, questionnaires associated with malnutrition & quality of life and body composition (obtained by Bioelectrical Impedance Vector Analysis) was performed before and after high-dose cisplatin chemotherapy combined with radiotherapy in 60 patients affected by head and neck cancer. Oral nutritional supplements were used to reach the correct number of daily calories and proteins.Results and discussionAll patients completed radiotherapy as planned and the 96,4% of them did not interrupt chemotherapy for toxicity, reaching a total dose of at least 200mg/m2. Despite a rapid deterioration of body composition during treatment, nutritional support helped patients to maintain (or in some cases improve) anthropometric parameters from the end of chemoradiotherapy to the following 3 months. Low prealbumin and albumin pre-treatment led to higher risk of toxicities with consequent reduction of cisplatin dose intensity, whereas weight at the end of the treatment seems to be an interesting predicting factor for disease free and overall survival (p=0.007; p=0.015).